Empirical and methodological foundations on the impact of climate-smart agriculture on food security studies: Review - Girma Tilahun; Amare Bantider; Desalegn Yayeh (Heliyon)
The progress of Ethiopia’s agriculture is constrained by climate change leaving smallholder farmers vulnerable. As a panacea to the challenge, development institutions, governments, and research organizations are progressively promoting climate-smart agriculture (CSA) to maximize productivity, increase the resilience of livelihoods and farming systems (adaptation), and minimize or stop greenhouse gas emissions to the atmosphere (mitigation). This review synthesized knowledge on the prospects of CSA and climate change in addressing the adverse effects of climate change and variability by revising 99 peer-reviewed journal articles. The results depict that smallholder farmers in Sub-Saharan Africa are highly impacted due to their reliance on the rain-fed agriculture production system. From several available CSA technologies in the study area, the review found that small-scale irrigation is the dominant option promoted in addition to improved animal husbandry and other technologies. Secondly, adoption differs across farmers and there can never be a one-size-fits-all approach in promoting adoption in farming societies. Thirdly, the key to spearheading the adoption of CSA is the active involvement of all actors along the value chain from the buyers to input suppliers of agricultural commodities. Moreover, the review indicated that development partners and the government have played a crucial role as evidenced by the CSA roadmap that supports CSA initiatives. Future CSA research should focus on agroecology and area-specific practices using simulation analysis and resource programming for a wider policy implication.